The plight of Taozhou Muslims: - Hasan Muhammad Maliwu (2013)

(untitled)
Taozhou Incursion 1929 is a disastrous calamity befallen Muslims in Gansu Province. In the Incursion, nearly 7,000 Muslim families were destroyed, and more than 60,000 innocent Muslims were slaughtered. From1928 to 1932, Taozhou Muslim community endured affliction, dispersion, diffusion as well as effacing, homicide, and capital punishment which Hui Muslims were and are still exposed to by the Han-Tibetan terrorist and its allies. Even after the Incursion, Muslims in 34 villages of Taozhou were never allowed to return their homes.